Quantitative lung perfusion blood volume using dual energy CT–based effective atomic number (Zeff) imaging. Issue 11 (22nd October 2021) - Li, Ke; Li, Yinsheng; Qi, Zhihua; Garrett, John W.; Grist, Thomas M.; Chen, Guang‐Hong
Abstract: Background: Iodine material images (aka iodine basis images) generated from dual energy computed tomography (DECT) have been used to assess potential perfusion defects in the pulmonary parenchyma. However, iodine material images do not provide the needed absolute quantification of the pulmonary blood pool, as materials with effective atomic numbers ( Z eff ) different from those of basis materials may also contribute to iodine material images, thus confounding the quantification of perfusion defects. Purpose: (i) To demonstrate the limitations of iodine material images in pulmonary perfusion defect quantification and (ii) to develop and validate a new quantitative biomarker using effective atomic numbers derived from DECT images. Methods: The quantitative relationship between the perfusion blood volume (PBV) in pulmonary parenchyma and the effective atomic number ( Z eff ) spatial distribution was studied to show that the desired quantitative PBV maps are determined by the spatial maps of Z eff as PB V Z eff ( x ) = a Z eff β ( x ) + b, where a, b, and β are three constants. Namely, quantitative PB V Z eff is determined by Z eff images instead of the iodine basis images. Perfusion maps were generated for four human subjects to demonstrate the differences between conventional iodine material image‐based PBV (PBViodine ) derived from two‐material decompositions and the proposed PB V Z eff method. Results: Among patients with pulmonary emboli, the proposed PB V Z eff maps clearly show the perfusion defects while the PBViodine maps do not. Additionally, when there are no perfusion defects present in the derived PBV maps, no pulmonary emboli were diagnosed by an experienced thoracic radiologist. Conclusion: Effective atomic number–based quantitative PBV maps provide the needed sensitive and specific biomarker to quantify pulmonary perfusion defects.